The APELOGI Impact: A Strategy to Enhance Senior High School Students' Digital Literacy in the Era of Educational Transformation - Sapto Rosadi; Sholeh Hidayat; Enggar Utari (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2026)
Digital transformation in education demands that students have strong digital literacy as part of 21st-century competencies. This study aims to analyze and test the effectiveness of the APELOGI application in improving the digital literacy of high school students. APELOGI is an interactive Android-based learning application featuring learning videos, offline access to materials, artificial intelligence-based question-and-answer services (Tanya Gemini AI), comprehension exercises via Google Forms, systematic user instructions, and an attractive interface design. This study used a quasi-experimental design with a quantitative approach and involved 10th-grade students as the research sample. Data were collected through pre-test and post-test questionnaires compiled based on digital literacy indicators from the Ministry of Communication and Informatics. Data analysis was conducted using gain score calculations to identify improvements in students' digital literacy skills. The results showed a significant increase in overall digital literacy skills, particularly in the dimensions of digital ethics and digital culture, which were in the high category. These findings indicate that APELOGI is an effective technology-based learning strategy. The implication is that this application can be integrated into learning practices to strengthen students' digital literacy competencies and support the implementation of adaptive, innovative, and sustainable educational transformation.